Phosphine‐Stabilized Pnictinidenes. Issue 56 (20th August 2021) - Raiser, Dominik; Eichele, Klaus; Schubert, Hartmut; Wesemann, Lars
Abstract: The reaction of the intramolecular germylene‐phosphine Lewis pair (o‐PPh2 )C6 H4 GeAr* (1 ) with Group 15 element trichlorides ECl3 (E=P, As, Sb) was investigated. After oxidative addition, the resulting compounds ( o ‐PPh2 )C6 H4 (Ar*)Ge(Cl)ECl2 (2 : E=P, 3 : E=As, 4 : E=Sb) were reduced by using sodium metal or LiHBEt3 . The molecular structures of the phosphine‐stabilized phosphinidene ( o ‐PPh2 )C6 H4 (Ar*)Ge(Cl)P (5 ), arsinidene ( o ‐PPh2 )C6 H4 (Ar*)Ge(Cl)As (6 ) and stibinidene ( o ‐PPh2 )C6 H4 (Ar*)Ge(Cl)Sb (7 ) are presented; they feature a two‐coordinate low‐valent Group 15 element. After chloride abstraction, a cyclic germaphosphene [( o ‐PPh2 )C6 H4 (Ar*)GeP] [B(C6 H3 (CF3 )2 )4 ] (8 ) was isolated. The 31 P NMR data of the germaphosphene were compared with literature examples and analyzed by quantum chemical calculations. The phosphinidene was treated with [ i Bu2 AlH]2, and the product of an Al−H addition to the low‐valent phosphorus atom ( o ‐PPh2 )C6 H4 (Ar*)Ge(H)P(H)Al(C4 H9 )2 (9 ) was characterized. Abstract : Treating a germylene‐phosphine Lewis pair, 1, with trichlorides of phosphorus, arsenic, and antimony allowed the isolation of oxidative addition products. Reduction of these compounds with sodium metal or LiBHEt3 led to the synthesis of a phosphinidene, an arsinidene and a stibinidene. After halide abstraction, a germaphosphene, 8, was isolated, and its 31 P NMR data were analyzed by using quantum chemical calculations. The product of an Al−H addition was found upon treating the phosphinidene with [ i Bu2 AlH]2 .